Preliminary Phytochemical Screening & Eveluation Anthelmintic Property of Embelia Ribes Burn. (In Vitro) - Linthuja, Y.; Thayalini, T.; Kokulavashiny, V. (University of Jaffna, 2024)
Helminthiasis is one of the most common parasitic infections worldwide. "Although antihelminthic drugs are used to treat helminthiasis, they were attributed to severe side effects. As a result, finding an alternative drug for the treatment of helminths from natural resources is inevitable. This study aimed to evaluate the anthelmintic potential of E.ribes and its phytochemical composition. Decoction and methanolic extract of seed of E.ribes were prepared and subjected to in vitro valuation of anthelmintic potential against earthworm (Eisenia fetida) by analysis the paralysis me and death time. Furthermore, the presence of phytochemicals such as saponin, tannin, Bonoids, glycosides and terpenoids were screened. lts indicated that both decoction and methanolic extract of E.ribes exhibited anthelminticity against earthworms on concentration-dependent manner. Moreover, higher concentrations ecoction at1/5 in dilution showed paralysis and death of the earthworm at 50.36+0.33 minutes 50.27±0.19 minutes, respectively. Whereas 2.5 mg/ml concentrations of methanolic extract bited paralysis and death of the worm at 60.20+0.33 minutes and 60.36±0.19 minutes, respectively. both decoction and methanolic extract contains saponin, tannin flavonoids terpenoids Results revealed that both decoction and methanolic extract of E.ribes exhibited anthelmintic activity against earthworms, however, further experimentation with other helminths to be evaluated in the future.
Keywords: Anthelmintic; Embelia ribes; Decoction Methanolic extract; Phytochemicals